Pengaruh Terapi Aktivitas Kelompok Sosialisasi (TAKS) terhadap Kemampuan Interaksi Sosial pada Lansia dengan Kesepian di Pelayanan Sosial Lanjut Usia (PSLU) Jember (The Effects of Socialization Group Activity Therapy (SGAT) toward Ability of Social Intera - Wahyu Elok Pambudi; Erti Ikhtiarini Dewi; Lantin Sulistyorini (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Elderly are people who over the age of 60 years old. The aging process of elderly will reduce the normal function of the body. This situation can make ability of social interaction being down and elderly feel lonely. Socialization Group Activity Therapy (SGAT) aims to increase the social relationship in the group gradually. The aim of this research was to analyze the effects of SGAT toward ability of social interaction of elderly with loneliness at nursing home Jember. This research used pre experimental method with one group pretest posttest design. There were 19 elderly who participate as the samples of this research. The samples were taken by using purposive sampling technique. The data were analyzed with dependent t-test, with the increasing of the average value ability of social interaction was 14,11 (22.3 - 37.32). The ability of social interaction of elderly with loneliness after getting SGAT was 94,7% had a good ability of social interaction. The result showed that p value = 0,0005 (CI 95%). The conclusion is there were significant effects of SGAT toward ability of social interaction of elderly with loneliness at nursing home Jember. This research recommended the SGAT to increase the ability of social interaction of elderly with loneliness. Keywords: Elderly with Loneliness, SGAT, Ability of Social Interaction